2007
DOI: 10.1007/s00204-007-0237-y
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effects of garlic and Panax ginseng extract standardized with ginsenoside Rg3 on the genotoxicity, biochemical, and histological changes induced by ethylenediaminetetraacetic acid in male rats

Abstract: Ethylenediaminetetraacetic acid (EDTA) is widely used in food and other industries to sequester metal ions and to prevent their disadvantageous effects. The objective of the current study was to evaluate the protective effect of Panax ginseng extract standardized with ginsenoside Rg3 (ginsenoside Rg3 content was 3.6% w/w, i.e., 36 microg/mg P. ginseng extract) and garlic against EDTA-induced biochemical, genotoxic, and histological changes in rats. Forty male rats were divided into eight treatment groups and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…Ginsenosides are the major active components of ginseng, which have been shown to have a variety of beneficial effects, including immunomodulatory [2], antioxidant [44], anti-stress [2], anti-inflammatory [44], anti-aging activities [2], and anti-fatigue [2], et al In addition, ginsenoside Rg3 is a relatively safe and effective medicine [5]. Some results demonstrated that ginsenoside Rg3 not only had no side effects on marrow, heart, lung, liver, kidney, and the nervous system [5], but also could improve the living quality of mice with tumor [6,30].…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenosides are the major active components of ginseng, which have been shown to have a variety of beneficial effects, including immunomodulatory [2], antioxidant [44], anti-stress [2], anti-inflammatory [44], anti-aging activities [2], and anti-fatigue [2], et al In addition, ginsenoside Rg3 is a relatively safe and effective medicine [5]. Some results demonstrated that ginsenoside Rg3 not only had no side effects on marrow, heart, lung, liver, kidney, and the nervous system [5], but also could improve the living quality of mice with tumor [6,30].…”
Section: Discussionmentioning
confidence: 99%
“…These compounds may have potential as novel prostate cancer therapeutic agents [2224]. Furthermore, ginsenoside Rg3 in mouse model studies has a preventive effect on DNA damage and cell death induced by cyclophosphamide [131] and has an inhibitory effect on genotoxicity, chemical and histological changes induced by ethylenediaminetetraacetic acid (EDTA), which is widely used in food [132]. The dosage used in these studies was 20 mg/kg and it was found that ginsenoside Rg3 alone did not induce any genotoxicity in mouse peripheral lymphocyte cells and bone marrow cells [131].…”
Section: Pharmacokinetics and Toxicity Issuesmentioning
confidence: 99%
“…For this RAPD PCR, five oligodecamers [17] (Table 1) were used. For each DNA extracted per animal, five PCR reactions with same conditions were performed.…”
Section: Methodsmentioning
confidence: 99%